THE IMPACT OF COMMUNICATIVE LANGUAGE TEACHING ON STUDENTS SPEAKING SKILL (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This empirical study investigates the impact of Communicative Language Teaching (CLT) on the development of students’ speaking skills in English as a Foreign Language (EFL) classrooms. In the modern globalized world, English communication skills are essential for academic success and professional growth. However, many learners face difficulties in speaking due to traditional teachercentered approaches that focus primarily on grammar and memorization. This research examines how communicative teaching strategies influence learners’ oral performance, confidence, and classroom interaction.